HEYDAR ALİYEV WAS A LEADER FROM A YOUNG AGE - Svetlana Mammadova (World Scientific Reports, 2023)
Heydar Alirza oglu Aliyev was born on May 10, 1923 in Nakhchivan, Azerbaijan, in the family of a railway worker. The war did not allow him to finish his education. Aliyev defined the modern face of Azerbaijan with his political genius and left an indelible mark on the fate of our people. Unparalleled achievements as a result of his policy are obvious. Modern democratic, legal and secular state building in Azerbaijan, organization of civil society, return to national and moral values and development of science, education and culture are forever connected with the name of H. Aliyev. Heydar Aliyev has unparalleled services in the field of library building, which is an integral part of Azerbaijani culture. In the second half of the 20th century, the work done by Heydar Aliyev in the direction of development of library networks, centralization of libraries, development of library funds, improvement of library services to the population, strengthening of material and technical base of libraries and personnel potential in the republic is undeniable.